The Nagorno-Karabakh Conflict: A Legal Conundrum - Marsili, M. (3.º Encontro de Investigação e Desenvolvimento em Ciências Militares (ECM2021), 2021)
Reportedly, in the long-lasting Nagorno-Karabakh conflict there were serious violations of international law and international humanitarian law; all parties involved accused each other of war crimes. So far, for such alleged violations, no legal remedy was possible under the current international legal framework. This work analyzes the problem of the Nagorno-Karabakh conflict in the light of current international (humanitarian) law.